Risk assessment of energy transactions in wholesale electricity spot market of a generating company with bilateral contracts - Umali, Likha Ma. D.
The Electric Industry Reform Act (EPIRA) of 2001 created the Wholesale Electricity Spot Market (WESM) for trading electricity as a commodity. It was designed to promote competition to bring down the prices of electricity to a level that can be achieved through market forces. In a competitive market, the players are facing risks that must be measured and managed. This research developed a methodology to quantify the financial risk for a GENCO with several generating units in a competitive electricity market using Value-at-Risk (VaR). A Monte Carlo simulation technique was used to calculate VaR by modeling different pricing scenarios, bids and schedules of generation. Hourly market prices are forecasted using Artificial Neural Network model and bidding strategies are constructed using Price-Based Unit Commitment method. The risk calculation method was tested for two systems: the California Power Market and Philippine WESM. The prices of the former were applied to a 36 unit test system and the results were successfully verified with published literature. The latter was applied to the three PSALM trading teams which were simplified to consist only of the fossil-fired power plants of NPC's Independent Power Producers. The results indicate that VaR is influenced by two factors: the bidding strategies for both bid quantity and price and the accuracy of the forecast of the 24 hour market prices. This paper also shows that adding more units does not necessarily lower the risk for a particular PSALM trading team. VaR enables the participant to lessen the variability of its revenue and profit distributions by bidding on the forecasted price as market volatility increases. This is a crucial strategy in a highly volatile market such as the Philippine WESM whos prices at its current state are difficult to forecast.